Broadcast Media in Promoting Environmental Awareness: A Study of Yobe State Broadcasting Cooperation Damaturu (YBC), Nigeria - Maidunoma, Zannah; Falmatami, Kyari Sheriff (NIU Journal of Humanities; Vol 3 No 1 (2018): KIU Journal of Humanities, Vol. 3 No. 1, March 2018, 2018)
The mass media play an important role in promoting environmental awareness. In the past decades, environmental awareness have gained media attention. Due to increasing media coverage, our society is becoming more aware of the effects that our activities put on the health of the environment. In this regard the media has a big role to play in making people aware of environment issues. The term Mass Media may be defined as the means of communication that reach large number of people in a short time, such as television, radio, newspapers, magazines. Nowadays, the role of Media has leaned towards informing, educating, sensitizing, mobilizing and creating awareness about the environmental challenges in the society that we face in our day to day life. Broadcast Media are powerful tools that can portray the real picture for the audience to visualize about the various environmental issues like sanitation and hygiene practices, global warming, waste management, safe water, climate change, deforestation, air pollution, afforestation. Which are of utmost importance to our ecology. The objective of this paper is to examining the role of broadcast media in promoting environmental awareness in Yobe state, Nigeria. This research was based on agenda setting theory. Two research instruments were used to obtain data. They were interviews and questionnaire. The responses obtained from the interviews were used as part of the discussion of findings. Purposive sampling methods were adopted for the study. These techniques enable the researcher to select the target respondents from a large group. The collected data is coded, edited and analyzed with the help of Statistical Package for the Social Sciences (SPSS) software. Keywords: Broadcasting Media, Environmental Awareness.